المنهجية النبوية القيادية في إدارة الأزمات: Arabic: The Prophetic Methodology of Leadership in Crisis Management - Ul Haq, Dr Ikram; Qadir Haroon, Dr Abdul (Al Basirah, 2022)
The leadership qualities conspicuously come to the surface, whenever there is a need for conflict resolution or there is a case of risk management, in focus. The Holy Prophets, appointed by God Almighty, have been always an example of leadership in social reforms and purgation from moral ailments in human society. Almost all human societies have been facing crisis management challenges in their communal life. The Muslim society from its very inception faced the same challenges, however, those were addressed by the Holy Prophet Muhammad (PBUH) in such a way that it has become a role model for the Muslims in particular and for humanity, in general. The following study explores lessons from the Seerah Role Model, the style of leadership, and especially the methods for crisis management.